The Challenges of Eradicating Pediatric Helicobacter pylori Infection in the Era of Probiotics - Lorena Elena Meliț; Cristina Oana Mărginean; Maria Oana Săsăran (Children, 2022)
Helicobacter pylori (H. pylori), the most common infection of childhood, results in life-threatening complications during adulthood if left untreated. Most of these complications are related to H. pylori-induced chronic inflammation. The dysbiosis caused by H. pylori is not limited to the gastric microenvironment, but it affects the entire gastrointestinal tract. Eradication of H. pylori has recently become a real challenge for clinicians due to both the persistent increase in antibiotic resistance worldwide and the wide spectrum of side effects associated with the eradication regimens resulting; therefore, there is an urgent need for more effective and less noxious treatment options. Thus, probiotics might be a promising choice in both adults and children with H. pylori infection since their role in improving the eradication rate of this infection has been proved in multiple studies. The positive effects of probiotics might be explained by their abilities to produce antimicrobial compounds and antioxidants, alter local gastric pH, and subsequently decrease H. pylori colonization and adherence to gastric epithelial cells. Nevertheless, if used alone probiotics do not considerably increase the eradication rate.